Pengaruh Kinerja Keuangan Daerah Terhadap Belanja Modal Untuk Pelayanan Publik Dalam Perspektif Teori Keagenan - Riswan RISWAN; Anthony Affandi (Jurnal Akuntansi dan Keuangan, 2014)
Fiscal capacity in the financial performance of the show , can be used as a tool to measure the success of carrying out local autonomy . The progress of the region one of which can be reviewed with good economic growth . The purpose of this study was to obtain empirical evidence on the influence of financial performance of the capital expenditure for public services at District / Municipal Se - Sumatra . Tests were conducted at 151 County / City of Se - Sumatra through quantitative analysis with simple regression . financial performance is measured by the ratio of the area of financial independence , financial effectiveness and efficiency ratios finances . While capital expenditures for public services is measured by the amount of capital for public service in the budget . The results showed that the financial performance of the positive effect on capital expenditures for public services at District / Municipal Se - Sumatra . Therefore, local governments should prioritize the financial performance of local governments to rise local capital expenditures.